Effects of emotional intelligence and supportive text messages on academic outcomes in first-year undergraduates - Joanne Hudson (Journal of Further and Higher Education, 2017)
An increase in the number of students entering higher education has intensified the need for targeted strategies to support a wider range of student requirements. Current research suggests that emotional intelligence (EI) may be associated with academic success, progression and retention in university students but the use of EI screening as a prospective measure of success requires further investigation. This study evaluates the utility of prospective EI screening to predict progression rates, mean grades, attendance and online engagement in a sample of first-year undergraduate students enrolled on the same degree programme (N = 358). A supportive text messaging intervention was employed during potentially stressful periods of the academic year with a subsection of participants (n = 60) who demonstrated low total EI scores relative to the cohort. Results showed no effects of EI classification on progression rates, mean grades, attendance or online engagement (all p > 0.418). Alternatively, the text messaging intervention was associated with significant improvements compared with a matched control group for progression rates (p = 0.027), mean grades (p = 0.026) and attendance (p = 0.007). The frequency of access to the virtual learning environment also tended to be higher in the intervention group compared with the control group (p = 0.059). In conclusion, this study did not identify any benefits of EI screening as a prospective indicator of student success but provides encouraging indications that a text messaging support intervention could help to improve progression rates, mean grades, attendance and online engagement in first-year undergraduate students. Further research is warranted to develop these proof-of-concept findings.